SUATU PENDEKATAN MONETER TERHADAP PERTUMBUHAN EKONOMI PADA PEREKONOMIAN TERBUKA KECIL DENGAN KONTROL MODAL: STUDI KASUS INDONESIA 2010.1-2014.12 - Aris Soelistyo (Jurnal Ekonomi Pembangunan, 2015)
The purpose of this study is to formulate the monetary model of the economic growth in a small open economy (small open economy) with a free exchange rate system (flexible exchange rate system) and capital mobility is not perfect (imperfect capital mobility), as well as the factors that influence economic growth, exchange rates and interest rates with monetary approach (mathematically and empirically).This study uses a structural analysis approach to vector autoregresion with monthly data Indonesia in 2010-2014. The empirical results reveal that changes in the money supply is a significant negative effect on economic growth 0.1008 Indonesia. Moreover, economic growth is affected by the magnitude of the previous period of economic growth significantly by 0.391825, where the magnitude of the effect is determined by the strength of the exchange rate in response to changes in interest rates Indonesia, the greater the exchange rate response to changes in interest rates, the weakening influence of the period of economic growth prior to economic growth. For a small open economy (small open economy) with a free exchange rate system (flexible exchange rate system), then the value of the rupiah per dollar exchange rate is influenced significantly by the amount of money in circulation (0.063318), the exchange rate value of the last period (0.746), and the interest rate the previous period (0.3424), the interest rate two previous periods (-0.305848).For situations of capital mobility is not perfect, then the variable interest rate is treated as endogenous variables, the empirical results show that the level of BI rate significantly influenced only by the BI rate the previous month (1.4526) and the interest rate of the previous two months (0.524)